The Importance Of Iodine Deficiency And Thyroid Diseases In Human Health - Zakirova Feruza Shuxratovna; Sardorova Nozila Otabekovna (International Journal of Medical Sciences And Clinical Research, 2025)
Iodine is an essential trace element for human health. Iodine performs various functions in the human body, especially in the production of thyroid hormones - triiodothyronine and thyroxine. In addition, it affects the immune, cardiovascular, reproductive and gastrointestinal systems. Studies have shown that thyroid diseases are associated with impaired functioning of all organs and tissues, especially a number of cardiovascular complications, which are associated with an increased risk of death. Recently, the effect of replacement therapy on the cardiovascular system in cases of thyroid hormone deficiency has been the subject of much debate and different opinions.